The Combination of Cyst Fluid Carcinoembryonic Antigen, Cytology and Viscosity Increases the Diagnostic Accuracy of Mucinous Pancreatic Cysts - Oh, Se Hun (Gut Liver, 2017)
BACKGROUND/AIMS: The objective of this study was to investigate the value of cyst fluid carcinoembryonic antigen (CEA) in combination with cytology and viscosity for the differential diagnosis of pancreatic cysts. METHODS: We retrospectively reviewed our data for patients who underwent endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) and cyst fluid analysis. We investigated the sensitivity, specificity and accuracy of the combination of cyst fluid CEA, cytology and viscosity testing. RESULTS: A total of 177 patients underwent EUS-FNA and cyst fluid analysis. Of these, 48 subjects were histologically and clinically confirmed to have pancreatic cysts and were therefore included in the analysis. Receiver operator curve analysis demonstrated that the optimal cutoff value of cyst fluid CEA for differentiating mucinous versus nonmucinous cystic lesions was 48.6 ng/mL. The accuracy of cyst fluid CEA (39/48, 81.3%) was greater than the accuracy of cytology (23/45, 51.1%) or the string sign (33/47, 70.2%). Cyst fluid CEA in combination with cytology and string sign assessment exhibited the highest accuracy (45/48, 93.8%). CONCLUSIONS: Cyst fluid CEA was the most useful single test for identifying mucinous pancreatic cysts. The addition of cytology and string sign assessment to cyst fluid CEA increased the overall accuracy for the diagnosis of mucinous pancreatic cysts.